Intellectual Education in Islam: Analysis of Ulu al-Albab Verses in the Qur'an - Firdaw Buerahen, Nur; Syarifah, Syarifah (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2024)
Education is considered one of the primary values in Islam, with particular emphasis on the development of intellectuality. The concept of Ulu al-Albab, which literally means "people of understanding," is often mentioned in the Qur'an as a symbol of wisdom and deep understanding. This paper aims to analyze the verses that mention Ulu al-Albab in the context of intellectual education in Islam, using a classical Qur'anic exegesis approach, particularly the Al-Maraghi interpretation. Research Method: This study employs a qualitative approach focusing on the textual analysis of the Qur'an. The primary data used are the verses that mention Ulu al-Albab in the Qur'an, which are then deeply analyzed using the Al-Maraghi interpretation. Results and Discussion: The analysis of the verses mentioning Ulu al-Albab indicates that intellectual education in Islam emphasizes the importance of developing intellect and profound understanding of religious teachings and the surrounding world. These verses also highlight the importance of reflection, reasoning, and critical thinking in achieving true understanding.